Can mobile and biometric payments replace cards in the Korean offline payments market? Consumer preference analysis for payment systems using a discrete choice model. (May 2019) - Kim, Minji; Kim, Seho; Kim, Junghun
Highlights: Consumers prefer mobile payments over biometric payments. Consumers prefer cards over mobile payments, biometric payments and cash. Overall attribute level of mobile and biometric payment systems should be developed. Improvement in technological competitiveness and infrastructure is necessary. Abstract: The convenience of mobile and biometric payments are making these systems increasingly popular in the Korean offline payments market. However, the diffusion of alternative offline payment systems such as mobile or biometric payments is slower than expected. Therefore, the purpose of this study is to analyze consumer preferences for payment systems and examine the effects of consumers' characteristics on the marginal utility of mobile and biometric payments. It uses the discrete choice experiment consisting of five major attributes to estimate preference parameters, and analyzes the data using the mixed logit model. The results show that consumers preferred cards to mobile and biometric payments even if they displayed the same level of related attributes. The scenario analysis results based on consumer preferences also showed the need to develop the overall attribute level of mobile and biometric payments. Furthermore, consumers' positive attitude or innovativeness toward hi-tech products has a significantly positive effect on preferences for alternative payments. Based on the results, this study provides theoretical implications for consumer preference studies on payment systems and proposes market strategies for the diffusion of major next-generation payment systems from multiple aspects.